Brother Otto Mäeder: an examination and evaluation of his work as a rock art recorder in South Africa - Flett, A.; Letley, P. (Southern African Humanities, 2007)
This paper examines and evaluates Brother Otto Mäeder as a rock art recorder. It reviews the perceptions created by Raymond Dart and perpetuated by subsequent researchers that Brother Otto had quaint and fanciful ideas about the art. This study indicates that Brother Otto not only carried out important recordings of rock art near Underberg, KwaZulu-Natal, and in the Kei River, Eastern Cape Valley but also used the few opportunities offered to him to research Bushman culture and art. He offered some important ideas about the origins, techniques, and meanings of the art and investigated the pigments used. By comparing recent digital photographs of the art with Brother Otto's copies it is evident that he was a faithful recorder and deserves to be acknowledged as such. Also commented on are a copy by George W. Stow, and the work of Brother Otto's contemporary Father Schweiger who subscribed to Dart's theories about foreigners depicted in the art. The study highlights the fact that Brother Otto's work and the Keilands area need further, urgent research attention.